Antibacterial bioadhesive layer-by-layer coatings for orthopedic applications - Carvalho, A. L. (2016)
In this study, thin LbL films were produced by combining the adhesive properties of the hyaluronic acidâ dopamine conjugate with the bioactivity and bactericidal properties of silver doped bioactive glass nanoparticles. The build-up of these films was investigated by quartz crystal microbalance with dissipation monitoring. LbL coatings were then constructed on a glass substrate for further characterization. We found that these antimicrobial bioinspired films display enhanced adhesive strength.Â In vitroÂ bioactivity tests were performed by immersing them in simulated body fluid solution for 14 days where the constructed films promoted the formation of a bone-like apatite layer. From microbiological assays, it was found that coatings containing silver doped nanoparticles exhibited a remarkable antibacterial effect againstÂ Staphylococcus aureusÂ andÂ Escherichia coliÂ cultures. Finally,Â in vitroÂ cellular behavior tests showed enhanced cell adhesion, proliferation and viability for these antibacterial bioadhesive films. Therefore, the constructed thin films showed promising properties and evidenced great potential to be used as coatings for orthopedic implants.